"FIFA 11 for Health" for Europe in the Faroe Islands: Effects on health markers and physical fitness in 10‐ to 12‐year‐old schoolchildren. (8th June 2018) - Skoradal, M.‐B.; Purkhús, E.; Steinholm, H.; Olsen, M. H.; Ørntoft, C.; Larsen, M. N.; Dvorak, J.; Mohr, M.; Krustrup, P.
Abstract : We evaluated effects of the school‐based intervention "FIFA 11 for Health" for Europe on health and fitness profile in 10‐ to 12‐year‐old Faroese schoolchildren. 392 fifth‐grade children were randomized into a control group (CG: n = 100, 11.1 ± 0.3 years, 149.0 ± 6.7 cm, 42.4 ± 10.2 kg) and an intervention group (IG: n = 292, 11.1 ± 0.3 years, 150.6 ± 6.9 cm, 44.2 ± 9.4 kg). IG underwent an 11‐week intervention in which 2 weekly sessions of 45 minutes were included in the school curriculum focusing on health aspects, football skills, and 3v3 small‐sided games. CG continued with their regular activities. Body composition, blood pressure, and resting heart rate, as well as Yo‐Yo intermittent recovery children's test (YYIR1C) performance, horizontal jumping ability and postural balance were assessed pre and post intervention. Systolic blood pressure decreased more (−2.8 ± 9.9 vs 2.9 ± 8.4 mm Hg, P  < .05) in IG than in CG. Lean body mass (1.0 ± 1.7 vs 0.7 ± 1.6 kg), postural balance (0.3 ± 3.9 vs −1.2 ± 5.9 seconds) and horizontal jump performance (5 ± 9 vs ‐5 ± 10 cm) increased more ( P  < .05) in IG than in CG. YYIR1C performance improved in CG (17%, 625 ± 423 to 730 ± 565 m) and IG (18%, 689 ± 412 vs 813 ± 391 m), but without between‐group differences. A within‐group decrease from 23.1 ± 8.4 to 22.5 ± 8.3% ( P  < .05) was observed in body fat percentage in IG only. In conclusion, the "FIFA 11 for Health" for Europe program had beneficial effects on SBP, body composition, jump performance and postural balance in 10‐ to 12‐year‐old Faroese schoolchildren, supporting the notion that school‐based football interventions can facilitate health of children in a small‐scale society and serve as an early step in the prevention of non‐communicable diseases.